2012
DOI: 10.5536/kjps.2012.39.3.207
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Dietary Protein Level on Laying Performance and Egg Quality in Japanese Quail

Abstract: This experiment was conducted to investigate the effects of various levels of dietary protein on laying performance and egg quality in laying quail. A total of six hundred forty 7-week-old laying type Japanese quail were divided into four groups with eight replicates per group (20 birds per replicate) and fed four diets differing in dietary protein levels (18, 20, 22 and 24%) with isocaloric corn-soybean meal-based diets for 8 weeks. The results showed no significant differences in feed intake and egg weight a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
(4 reference statements)
1
0
0
Order By: Relevance
“…The lack of significant effects of dietary ND on most blood parameters of laying quails, estimated herein, agrees with those of Oh et al (2012) they observed no significant effect of dietary protein (18, 20, 22 and 24%) on blood levels of glutamic-oxaloacetic transaminase, glutamic-pyruvic transaminase, blood urea nitrogen, albumin, and creatinine of Japanese quail hens. Similarly, Ismail et al (2015) found that feeding the high nutrient density diets (102.5, 105, 107.5 and 110%) had no significant effect on most blood parameters of laying hens.…”
Section: Carcass Measurements Of Quailssupporting
confidence: 91%
“…The lack of significant effects of dietary ND on most blood parameters of laying quails, estimated herein, agrees with those of Oh et al (2012) they observed no significant effect of dietary protein (18, 20, 22 and 24%) on blood levels of glutamic-oxaloacetic transaminase, glutamic-pyruvic transaminase, blood urea nitrogen, albumin, and creatinine of Japanese quail hens. Similarly, Ismail et al (2015) found that feeding the high nutrient density diets (102.5, 105, 107.5 and 110%) had no significant effect on most blood parameters of laying hens.…”
Section: Carcass Measurements Of Quailssupporting
confidence: 91%